RedUSe: reducing antipsychotic and benzodiazepine prescribing in residential aged care facilities. Issue 9 (14th May 2018) - Westbury, Juanita L; Gee, Peter; Ling, Tristan; Brown, Donnamay T; Franks, Katherine H; Bindoff, Ivan; Bindoff, Aidan; Peterson, Gregory M
Abstract: Objective: To assess the impact of a multi‐strategic, interdisciplinary intervention on antipsychotic and benzodiazepine prescribing in residential aged care facilities (RACFs). Design, setting: Prospective, longitudinal intervention in Australian RACFs, April 2014 – March 2016. Participants: 150 RACFs (with 12 157 residents) comprised the main participant group; two further groups were consultant pharmacists (staff education) and community pharmacies (prescribing data). Data for all RACF residents, excluding residents receiving respite or end‐stage palliative care, were included. Intervention: A multi‐strategic program comprising psychotropic medication audit and feedback, staff education, and interdisciplinary case review at baseline and 3 months; final audit at 6 months. Main outcome measure: Mean prevalence of regular antipsychotic and benzodiazepine prescribing at baseline, and at 3 and 6 months. Secondary measures: chlorpromazine and diazepam equivalent doses/day/resident; proportions of residents for whom drug was ceased or the dose reduced; prevalence of antidepressant and prn (as required) psychotropic prescribing (to detect any substitution practice). Results: During the 6‐month intervention, the proportion of residents prescribed antipsychotics declined by 13% (from 21.6% [95% CI, 20.4–22.9%] to 18.9% [95% CI, 17.7–20.1%]), and that of residents regularly prescribed benzodiazepines by 21% (from 22.2% [95% CI, 21.0–23.5%] to 17.6% [95% CI, 16.5–18.7]; each, P < 0.001). Mean chlorpromazine equivalent dose declined from 22.9 mg/resident/day (95% CI, 19.8–26.0) to 20.2 mg/resident/day (95% CI, 17.5–22.9; P < 0.001); mean diazepam equivalent dose declined from 1.4 mg/resident/day (95% CI, 1.3–1.5) to 1.1 mg/resident/day (95% CI, 0.9–1.2; P < 0.001). For 39% of residents prescribed antipsychotics and benzodiazepines at baseline, these agents had been ceased or their doses reduced by 6 months. There was no substitution by sedating antidepressants or prn prescribing of other psychotropic agents. Conclusions: The RedUSe program achieved significant reductions in the proportions of RACF residents prescribed antipsychotics and benzodiazepines. Trial registration: Australian New Zealand Clinical Trials, ACTRN12617001257358.